IMPLEMENTASI PEMBELAJARAN IPA BERBASIS ONLINE LEARNING BERBANTUAN E-BOOK INTERAKTIF UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF - Nur Rahmah Sangkala; Musawwir Usman; Akhmad Syakur (Universitas Cokroaminoto Palopo, 2026)
Digital transformation in education encourages the integration of technology in science learning to support the development of 21st-century skills, one of which is creative thinking skills. This study aimed to determine the improvement of students’ creative thinking skills through the implementation of science learning assisted by an interactive e-book on the subtopic of Nutrition in Food. This study employed a pre-experimental research design using the One Group Pretest-Posttest Design. The research sample consisted of 23 eighth-grade students of SMP Piri 1 Yogyakarta selected using a saturated sampling technique. Data were collected using an essay-based creative thinking skills test covering the aspects of fluency, flexibility, originality, and elaboration. The data were analyzed using descriptive quantitative analysis with n-gain calculation. The results showed that the implementation of science learning assisted by an interactive e-book was able to improve students’ creative thinking skills. The n-gain results indicated that 3 students were categorized as high and 20 students were categorized as moderate. Improvements also occurred in each aspect of creative thinking skills, namely fluency by 30.5%, flexibility by 18.9%, originality by 26.1%, and elaboration by 22.3%. The use of interactive e-books in science learning was able to create a more engaging, interactive, and flexible learning experience, thereby supporting the development of students’ creative thinking skills.